Characteristics of Non-Audit Services and Financial Restatements in Malaysia - Abdul Wahab, Effiezal Aswadi; Gist, W.; Abdul Majid, W.Z. (Elsevier Ltd, 2014)
Various types of purchased non-audit services (NAS) and their recurring nature affect the likelihood of financial statement restatements in Malaysia. Based on 953 firm-year observations during the period 2007–2009, evidence of a negative relationship between non-audit fees and financial statement restatements is provided. The purchase of both tax-related and audit-related NAS decreases the likelihood of restatements. Recurring (as opposed to non-recurring) tax-related and audit-related NAS are negatively and significantly related to the likelihood of restatements. These findings support our hypothesis that both types of NAS and their recurrence provide knowledge spillover, which enhances audit and financial reporting quality. When considering institutional settings, we find that politically connected firms are more likely to require financial restatements than non-politically connected firms, while audit committee independence and the purchase of tax-related, recurring tax-related and other NAS decrease this likelihood. The purchase of audit-related and recurring audit-related NAS and non-recurring other NAS decreases the likelihood of restatements for non-politically connected firms.